Distribution of blood pressure in school going children in rural area of Wardha district, Maharashatra, India - Taksande Amar; Chaturvedi Pushpa; Vilhekar Krishna; Jain Manish (Wolters Kluwer Medknow Publications, 2008)
Objectives: To study the blood pressure of school going children in a rural area and its relationship with the anthropometric indices. Methods : A prospective, cross-sectional study was carried out from November 2006 to December 2007 in the school going children between the ages of 6-17 years from eight different schools in the rural areas of Wardha district. The height, weight, systolic blood pressure (SBP), and diastolic blood pressure (DBP) were recorded in both sexes followed by complete clinical examination with special emphasis on cardiovascular system. Hypertension (HT) was defined as SBP or DBP exceeding the 95th percentile for age, gender, and height on at least three separate occasions, 1-3 weeks apart. SPSS software was used to analyze the data. Coefficient correlation tests were employed to assess the relation between BP and anthropometric variables. Results :Of 2643 school children, 1227 were boys and 1416 girls with a male to female ratio of 1:1.16. In boys, SBP and DBP increased with age except a marginal decline in SBP at the age of 17 years (-0.09) and decrease in the DBP (-1.29) at 16 years of age. In girls, SBP and DBP also increased with age except at 11 years, wherein there was a mild decrease in SBP (-0.09) as well as the DBP (-0.24). Correlation coefficient analysis showed highly significant positive correlation of height with SBP and DBP. There was a significant correlation of SBP and DBP with the weight, and body mass index (BMI). The prevalence of HT was 5.75% (i.e., 3.25% for systolic HT and 2.49% for diastolic HT). Conclusion : We recommend that there is a need for checking BP to detect HT in children, so that remedial measures can be initiated as early as possible.